Adverse drug events related to COX inhibitors in patients presenting at an emergency department: Cross-sectional study of prevalence and risk factors - Pfistermeister, Barbara; Dormann, H.; Patapovas, Andrius; Müller, Fabian; Sonst, A.; Gläser, Hartmut; Plank-Kiegele, Bettina; Bürkle, T.; Maas, Renke (Notfall und Rettungsmedizin, 2016)
Background: The use of cyclooxygenase (COX) inhibitors is increasingly common. Most of them are available for self-medication, either as analgesic or for cardio- and cerebrovascular prevention. Objectives: We aimed to analyze adverse drug events (ADE) related to COX inhibitors and the concomitant use of proton pump inhibitors (PPI) according to guidelines in patients presenting at an emergency department (ED). Methods: In a prospective study, 2262 patients presenting consecutively at the ED of a tertiary care university teaching hospital were evaluated by intensive chart review in order to detect and classify all ADE. In this cross-sectional analysis all patients taking COX inhibitors at home were evaluated further. Results: Of all evaluated patients, 753 (33.3 %) took COX inhibitors at home, 258 (34.3 %) with concomitant PPI. A total of 168 (22.3 %) patients suffered from at least one ADE related to COX inhibitors. The most common ADE observed were anemia (55.9 %) and gastrointestinal ADE (31.6 %, e. g., bleeding, gastritis, and ulcer). In 10.1 % of patients, a medication error (e. g., intake without proper clinical indication) contributed to the ADE and in 40.8 % of the ADE involved further contributing drugs. Only 38.8–42.1 % of patients with a high gastrointestinal risk were prescribed a PPI concomitantly. Conclusion: ADE related to COX inhibitors were found in every fifth patient taking COX inhibitors. One-tenth of all ADE involving COX inhibitors were related to medication errors. The guideline-based concomitant use of PPI was only in part implemented.
CRIS-Team Scopus Importer:2025-02-03
Keywords: Cyclooxygenase inhibitors; Drug–drug interaction; Gastrointestinal hemorrhage; Proton pump inhibitor; Self medication

Analysis of amino acid residues in the predicted transmembrane pore influencing transport kinetics of the hepatic drug transporter organic anion transporting polypeptide 1B1 (OATP1B1) - Gruetz, Moritz; Sticht, Heinrich; Gläser, Hartmut; Fromm, Martin; König, Jörg (BBA - Biochimica et Biophysica Acta, 2016)
The hepatic uptake transporters OATP1B1 (SLCO1B1) and OATP1B3 (SLCO1B3) mediate the uptake of endogenous metabolites and drugs from blood into hepatocytes. Alterations of transport function are accompanied with variations in drug plasma concentrations and the risk of adverse drug effects. Thus, knowledge on amino acids determining substrate recognition or transport kinetics are important to predict alterations in transport kinetics. Therefore, we analyzed the charged amino acids His54 and Tyr169, both located at the extracellular entry of the predicted transmembrane pore of OATP1B1. Based on a computational analysis we established HEK293 cell lines overexpressing the mutant OATP1B1 proteins HEK-OATP1B1p.H54Q, -p.H54A, -p.Y169H and -p.Y169A and analyzed protein expression, localization and transport kinetics of the four OATP1B1 substrates bromosulfophthalein, estradiaol-17?-glucuronide, taurocholate and pravastatin. Consequences on transport were detected for all mutants and these were different for each amino acid exchange and for each substrate tested. For example, the exchange H54Q resulted in reduced transport for BSP (78% of wildtype OATP1B1 transport at 0.05?M, P<0.01) with reduced affinity to this substrate (Km value increases from 0.76?M to 8.04?M) but in stimulated E217?G transport (138% compared to wildtype transport at 10?M, P<0.001). Investigating amino acid exchanges located at the extracellular entry of the transport pore of the OATP1B1 protein we demonstrated that these residues are involved in modulating transport kinetics and this participation strongly depends on the substrate and not on the physicochemical character of the investigated amino acid.
EVALuna2:8698

Functional and Structural Relevance of Conserved Positively Charged Lysine Residues in Organic Anion Transporting Polypeptide 1B3 - Mandery, Kathrin; Sticht, Heinrich; Bujok, Krystyna; Schmidt, Ingrid; Fahrmayr, Christina; Balk, Bettina; Fromm, Martin; Gläser, Hartmut (Molecular Pharmacology, 2011)
The human organic anion transporting polypeptide 1B3 (OATP1B3), located in the basolateral membrane of hepatocytes, mediates the uptake of endogenous substrates such as taurocholate and drugs from blood into hepatocytes. The transport activity of OATP1B3 is influenced by positively charged amino acids, which are facing the central pore. Molecular modeling was performed to select conserved positively charged amino acids, which may influence transport activity and anchoring of OATP1B3 in the plasma membrane. The modeling revealed that Lys361 faces the pore, and Lys399 is oriented to the plasma membrane. Therefore, the mutants L361>A, L361>R, L399>A, and L399>R were generated using site-directed mutagenesis to investigate the impact of the positive charges on transport activity and anchoring in the membrane. Transport kinetic analyses for the substrates sulfobromophthalein and taurocholate showed a loss of function for the L361>A mutant, whereas the transport activity was maintained by the L361>R mutant, indicating that the positive charge at position 361 is important for transport activity of OATP1B3. Comparative modeling with OATP1A2 and OATP2B1 revealed that the pore size around this lysine residue is larger in OATP1A2 and smaller in OATP2B1 compared with OATP1B3, which could be related to the respective substrate spectra. Cell surface expression of L399>A and L399>R was decreased to 16 and 72% compared with wild-type OATP1B3 (p < 0.001), respectively, indicating that the positive charge of lysine at position 399 is necessary for an unimpaired cell surface expression. Furthermore, we provide a summary of amino acids, which influence the transport activity of OATP1B3.
EVALuna2:8639

Green tea ingestion greatly reduces plasma concentrations of nadolol in healthy subjects - Misaka, S.; Yatabe, J.; Müller, Fabian; Takano, K.; Kawabe, K.; Gläser, Hartmut; Yatabe, M. S.; Onoue, S.; Werba, J. P.; Watanabe, H.; Yamada, S.; Fromm, Martin; et al. (Clinical Pharmacology & Therapeutics, 2014)
This study aimed to evaluate the effects of green tea on the pharmacokinetics and pharmacodynamics of the ?-blocker nadolol. Ten healthy volunteers received a single oral dose of 30 mg nadolol with green tea or water after repeated consumption of green tea (700 ml/day) or water for 14 days. Catechin concentrations in green tea and plasma were determined. Green tea markedly decreased the maximum plasma concentration (Cmax) and area under the plasma concentration-time curve (AUC0-48) of nadolol by 85.3% and 85.0%, respectively (P < 0.01), without altering renal clearance of nadolol. The effects of nadolol on systolic blood pressure were significantly reduced by green tea. [(3)H]-Nadolol uptake assays in human embryonic kidney 293 cells stably expressing the organic anion-transporting polypeptides OATP1A2 and OATP2B1 revealed that nadolol is a substrate of OATP1A2 (Michaelis constant (Km) = 84.3 ?mol/l) but not of OATP2B1. Moreover, green tea significantly inhibited OATP1A2-mediated nadolol uptake (half-maximal inhibitory concentration, IC50 = 1.36%). These results suggest that green tea reduces plasma concentrations of nadolol possibly in part by inhibition of OATP1A2-mediated uptake of nadolol in the intestine.
EVALuna2:8680

Inhibitory Effects of Green Tea and (-)-Epigallocatechin Gallate on Transport by OATP1B1, OATP1B3, OCT1, OCT2, MATE1, MATE2-K and P-Glycoprotein - Knop, Jana; Misaka, Shingen; Singer, Katrin; Hoier, Eva; Müller, Fabian; Gläser, Hartmut; König, Jörg; Fromm, Martin (PLoS ONE, 2015)
Green tea catechins inhibit the function of organic anion transporting polypeptides (OATPs) that mediate the uptake of a diverse group of drugs and endogenous compounds into cells. The present study was aimed at investigating the effect of green tea and its most abundant catechin epigallocatechin gallate (EGCG) on the transport activity of several drug transporters expressed in enterocytes, hepatocytes and renal proximal tubular cells such as OATPs, organic cation transporters (OCTs), multidrug and toxin extrusion proteins (MATEs), and P-glycoprotein (P-gp). Uptake of the typical substrates metformin for OCTs and MATEs and bromosulphophthalein (BSP) and atorvastatin for OATPs was measured in the absence and presence of a commercially available green tea and EGCG. Transcellular transport of digoxin, a typical substrate of P-gp, was measured over 4 hours in the absence and presence of green tea or EGCG in Caco-2 cell monolayers. OCT1-, OCT2-, MATE1- and MATE2-K-mediated metformin uptake was significantly reduced in the presence of green tea and EGCG (P < 0.05). BSP net uptake by OATP1B1 and OATP1B3 was inhibited by green tea [IC50 2.6% (v/v) and 0.39% (v/v), respectively]. Green tea also inhibited OATP1B1- and OATP1B3-mediated atorvastatin net uptake with IC50 values of 1.9% (v/v) and 1.0% (v/v), respectively. Basolateral to apical transport of digoxin was significantly decreased in the presence of green tea and EGCG. These findings indicate that green tea and EGCG inhibit multiple drug transporters in vitro. Further studies are necessary to investigate the effects of green tea on prototoypical substrates of these transporters in humans, in particular on substrates of hepatic uptake transporters (e.g. statins) as well as on P-glycoprotein substrates.
EVALuna2:8693

Interaction of innovative small molecule drugs used for cancer therapy with drug transporters. - Fromm, Martin; Mandery, Kathrin; Gläser, Hartmut (British Journal of Pharmacology, 2012)
Multiple new small molecules such as tyrosine kinase, mammalian target of rapamycin (mTOR) and proteasome inhibitors have been approved in the last decade and are a considerable progress for cancer therapy. Drug transporters are important determinants of drug concentrations in the systemic circulation. Moreover, expression of drug transporters in blood-tissue barriers (e.g. blood-brain barrier) can limit access of small molecules to the tumour (e.g. brain tumour). Finally, transporter expression and (up)regulation in the tumour itself is known to affect local drug concentrations in the tumour tissue contributing to multidrug resistance observed for multiple anticancer agents. This review summarizes the current knowledge on: (i) small molecules as substrates of uptake and efflux transporters; (ii) the impact of transporter deficiency in knockout mouse models on plasma and tissue concentrations; (iii) small molecules as inhibitors of uptake and efflux transporters with possible consequences for drug-drug interactions and the reversal of multidrug resistance; and (iv) on clinical studies investigating the association of polymorphisms in genes encoding drug transporters with pharmacokinetics, outcome and toxicity during treatment with the small molecules.

Interaction of oral antidiabetic drugs with hepatic uptake transporters: focus on organic anion transporting polypeptides and organic cation transporter 1. - Bachmakov, Iouri; Gläser, Hartmut; Fromm, Martin; König, Jörg (Diabetes, 2008)
The uptake of drugs into hepatocytes is a key determinant for hepatic metabolism, intrahepatic action, their subsequent systemic plasma concentrations, and extrahepatic actions. In vitro and in vivo studies indicate that many drugs used for treatment of cardiovascular diseases (e.g., oral antidiabetic drugs, statins) are taken up into hepatocytes by distinct organic anion transporters (organic anion transporting polypeptides [OATPs]; gene symbol SLCO/SLC21) or organic cation transporters (OCTs; gene symbol SLC22). Because most patients with type 2 diabetes receive more than one drug and inhibition of drug transporters has been recognized as a new mechanism underlying drug-drug interactions, we tested the hypothesis of whether oral antidiabetic drugs can inhibit the transport mediated by hepatic uptake transporters. Using stably transfected cell systems recombinantly expressing the uptake transporters OATP1B1, OATP1B3, OATP2B1, or OCT1, we analyzed whether the antidiabetic drugs repaglinide, rosiglitazone, or metformin influence the transport of substrates and drugs (for OATPs, sulfobromophthalein [BSP] and pravastatin; for OCT1, 1-methyl-4-phenylpyridinium [MPP(+)] and metformin). Metformin did not inhibit the uptake of OATP and OCT1 substrates. However, OATP-mediated BSP and pravastatin uptake and OCT1-mediated MPP(+) and metformin uptake were significantly inhibited by repaglinide (half-maximal inhibitory concentration [IC(50)] 1.6-5.6 micromol/l) and rosiglitazone (IC(50) 5.2-30.4 micromol/l). These in vitro results demonstrate that alterations of uptake transporter function by oral antidiabetic drugs have to be considered as potential mechanisms underlying drug-drug interactions. OBJECTIVE RESEARCH DESIGN AND METHODS RESULTS CONCLUSIONS

Interplay between the prostaglandin transporter OATP2A1 and prostaglandin E2-mediated cellular effects - Bujok, Krystyna; Gläser, Hartmut; Schuh, Wolfgang; Rau, Tilman; Schmidt, Ingrid; Fromm, Martin; Mandery, Kathrin (Cellular Signalling, 2015)
Prostaglandins such as prostaglandin E2 (PGE2) play a pivotal role in physiological and pathophysiological pathways in gastric mucosa. Little is known about the interrelation of the prostaglandin E (EP) receptors with the prostaglandin transporter OATP2A1 in the gastric mucosa and gastric carcinoma. Therefore, we first investigated the expression of OATP2A1 and EP4 in normal and carcinoma gastric mucosa. Different PGE2-mediated cellular pathways and mechanisms were investigated using human embryonic kidney cells (HEK293) and the human gastric carcinoma cell line AGS stably transfected with OATP2A1. Colocalization and expression of OATP2A1 and EP4 were detected in mucosa of normal gastric tissue and of gastric carcinomas. OATP2A1 reduced the PGE2-mediated cAMP production in HEK293 and AGS cells overexpressing EP4 and OATP2A1. The expression of OATP2A1 in AGS cells resulted in a reduction of [(3)H]-thymidine incorporation which was in line with a higher accumulation of AGS-OATP2A1 cells in S-phase of the cell cycle compared to control cells. In contrast, the expression of OATP2A1 in HEK293 cells had no influence on the distribution in the S-phase compared to control cells. OATP2A1 also diminished the PGE2-mediated expression of interleukin-8 mRNA (IL-8) and hypoxia-inducible-factor 1? (HIF1?) protein in AGS-OATP2A1 cells. The expression of OATP2A1 increased the sensitivity of AGS cells against irinotecan which led to reduced cell viability. Taken together, these data show that OATP2A1 influences PGE2-mediated cellular pathways. Therefore, OATP2A1 needs to be considered as a key determinant for the understanding of the physiology and pathophysiology of prostaglandins in healthy and tumorous gastric mucosa.
EVALuna2:6643

Organic anion transporting polypeptides and organic cation transporter 1 contribute to the cellular uptake of the flavonoid quercetin - Gläser, Hartmut; Bujok, Krystyna; Schmidt, Ingrid; Fromm, Martin; Mandery, Kathrin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)
Flavonoids such as quercetin and kaempferol mediate several health protective effects, e.g., anticancer effects. They are inhibitors of organic anion transporting polypeptides (OATP) and organic cation transporters (e.g., OCT2). However, little is known whether such transporters contribute to the cellular uptake of flavonoids. Therefore, we investigated the cellular uptake of kaempferol and quercetin using HEK293 cell lines stably expressing different human OATPs or OCT1. Kaempferol was not a substrate of any of the investigated transporters (OATP1A2, OATP1B1, OATP1B3, OATP2A1, OATP2B1, OATP3A1, OATP4A1, OATP5A1, and OCT1). Quercetin showed a significantly higher uptake into the HEK293-OATP1A2, HEK293-OATP2A1, HEK293-OATP2B1, and HEK293-OCT1 cells compared to control cells. The OATP1A2-, OATP2B1-, and OCT1-mediated quercetin uptake was inhibited by known inhibitors such as naringin, cyclosporin A, and quinidine, respectively. The cellular accumulation of quercetin into HEK293-OATP2A1 cells was not inhibited by prostaglandin E2 and diclofenac. The ionophore carbonyl cyanide 4-(trifluoromethoxy)phenylhydrazone (FCCP) reduced the net uptake of quercetin by increasing the uptake in the HEK293-control cells and causing no significant change in the HEK293-OATP2B1 cells indicating that quercetin follows the FCCP-driven proton flux through the plasma membrane. In addition to passive diffusion, the SLC transporters OATP1A2, OATP2B1, and OCT1 contribute to cellular accumulation of quercetin.
EVALuna2:8686

Prostaglandin E2 stimulates the epithelial sodium channel (ENaC) in cultured mouse cortical collecting duct cells in an autocrine manner - Mansley, Morag; Niklas, Christian; Nacken, Regina; Mandery, Kathrin; Gläser, Hartmut; Fromm, Martin; Korbmacher, Christoph; Bertog, Marko (Journal of General Physiology, 2020)
Prostaglandin E2 (PGE2) is the most abundant prostanoid in the kidney, affecting a wide range of renal functions. Conflicting data have been reported regarding the effects of PGE2 on tubular water and ion transport. The amiloride-sensitive epithelial sodium channel (ENaC) is rate limiting for transepithelial sodium transport in the aldosterone-sensitive distal nephron. The aim of the present study was to explore a potential role of PGE2 in regulating ENaC in cortical collecting duct (CCD) cells. Short-circuit current (ISC) measurements were performed using the murine mCCDcl1 cell line known to express characteristic properties of CCD principal cells and to be responsive to physiological concentrations of aldosterone and vasopressin. PGE2 stimulated amiloride-sensitive ISC via basolateral prostaglandin E receptors type 4 (EP4) with an EC50 of ∼7.1 nM. The rapid stimulatory effect of PGE2 on ISC resembled that of vasopressin. A maximum response was reached within minutes, coinciding with an increased abundance of β-ENaC at the apical plasma membrane and elevated cytosolic cAMP levels. The effects of PGE2 and vasopressin were nonadditive, indicating similar signaling cascades. Exposing mCCDcl1 cells to aldosterone caused a much slower (∼2 h) increase of the amiloride-sensitive ISC. Interestingly, the rapid effect of PGE2 was preserved even after aldosterone stimulation. Furthermore, application of arachidonic acid also increased the amiloride-sensitive ISC involving basolateral EP4 receptors. Exposure to arachidonic acid resulted in elevated PGE2 in the basolateral medium in a cyclooxygenase 1 (COX-1)-dependent manner. These data suggest that in the cortical collecting duct, locally produced and secreted PGE2 can stimulate ENaC-mediated transepithelial sodium transport.
CRIS-Team Scopus Importer:2020-06-05

Response to "the effect of green tea with exceptionally high catechin content on nadolol plasma concentration" - Misaka, S.; Yatabe, J.; Müller, Fabian; Takano, K.; Gläser, Hartmut; Yatabe, M. S.; Onoue, S.; Werba, J. P.; Watanabe, H.; Yamada, S.; Fromm, Martin; Kimura, J. (Clinical Pharmacology & Therapeutics, 2014)
EVALuna2:8684

The Nonmetabolized β-Blocker Nadolol Is a Substrate of OCT1, OCT2, MATE1, MATE2-K, and P-Glycoprotein, but Not of OATP1B1 and OATP1B3 - Misaka, Shingen; Knop, Jana; Singer, Katrin; Hoier, Eva; Keiser, Markus; Müller, Fabian; Gläser, Hartmut; König, Jörg; Fromm, Martin (Molecular Pharmaceutics, 2016)
Nadolol is a nonmetabolized ?-adrenoceptor antagonist and is a substrate of OATP1A2, but not of OATP2B1. However, other drug transporters involved in translocation of nadolol have not been characterized in detail. We therefore investigated nadolol as a potential substrate of the hepatic uptake transporters OATP1B1, OATP1B3, and OCT1 and of the renal transporters OCT2, MATE1, and MATE2-K expressed in HEK cells. Moreover, the importance of P-glycoprotein (P-gp) for nadolol transport was studied using double transfected MDCK-OCT1-P-gp cells. Nadolol was not transported by OATP1B1 and OATP1B3. In contrast, a significantly higher nadolol accumulation (at 1 and 10 ?M) was found in OCT1, OCT2, MATE1, and MATE2-K cells compared to control cells (P < 0.01). Km values for OCT2-, MATE1-, and MATE2-K-mediated nadolol uptake were 122, 531, and 372 ?M, respectively. Cimetidine (100 ?M, P < 0.01) and trimethoprim (100 ?M, P < 0.001) significantly inhibited OCT1-, OCT2-, MATE1-, and MATE2-K-mediated nadolol transport. The P-gp inhibitor zosuquidar significantly reduced basal to apical nadolol transport in monolayers of MDCK-OCT1-P-gp cells. In summary, nadolol is a substrate of the cation transporters OCT1, OCT2, MATE1, MATE2-K, and of P-gp. These data will aid future in vivo studies on potential transporter-mediated drug-drug or drug-food interactions with involvement of nadolol.
EVALuna2:8690